TB Patient Assistance Training For Health Cadres In Tuberculosis Eradication to Increase TB Health Cadre’s Self Efficacy in Sumenep - Menaldi, Adhityawarman; Giyani, Larissa Amira; Masturoh, Qaishum; Koentary, Andi Supandi Suaid (Jurnal Ecopsy, 2023)
The eradication of tuberculosis (TB) in Indonesia has been going on for a long time. Until 2021, Indonesia is still included in the top three countries with the highest TB burden in the world (WHO, 2021). One of the non-medical aspects that need attention is the skills of the personnel involved in assisting TB patients. Health cadres are one aspect of personnel who are very close to patients in time and proximity, but it is found that health cadres do not function optimally. Patient assistance skills training is the core of this training. There are seven main materials arranged in this training, namely helping professions, psychological disorders, and patient readiness, social power, listening skills, questioning skills, motivating skills, and relaxation guiding skills. This training was conducted in collaboration with the Stop TB Partnership Indonesia (STPI), on 12 and 13 January 2022 for 23 newly recruited health cadres in Sumenep Regency, East Java. The results of the pre- and post-training measurements showed an increase in self-efficacy scores between pre and post-training with p=0.049 and also a significant increase in strength subtest score with p=0.026. This shows that the skills training increases the participant’s self-efficacy on patients assistance.